2014
DOI: 10.5604/20815735.1127447
|View full text |Cite
|
Sign up to set email alerts
|

Performance in kimono grip strength tests among Brazilian Jiu-Jitsu practitioners from different levels

Abstract: SummaryIntroduction. In combat sports involving grappling, muscular strength is considered one of the most important physical components to be developed, specifically in upper limbs. The objective of our study was to examine if there are differences between elite and non-elite Brazilian Jiu-Jitsu practitioners, in two kimono grip strength endurance tests.Material and methods. Forty Brazilian Jiu-Jitsu practitioners were divided in four groups: Advanced; Non-Advanced; Recreational and Beginners. All participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Similarly, we found no differences in match characteristics between regional and international matches. Although it is not uncommon for advanced athletes to present superior physical characteristics compared to non-advance athletes (Corrêa da Silva et al, 2014;da Silva et al, 2012;da Silva Junior et al, 2019;Diaz Lara et al, 2014), this was not reflected in the match pace characteristics in our sample. A likely reason is that each athlete was matched with an opponent of similar skill and experience level, which may negate any major differences in athletic ability.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, we found no differences in match characteristics between regional and international matches. Although it is not uncommon for advanced athletes to present superior physical characteristics compared to non-advance athletes (Corrêa da Silva et al, 2014;da Silva et al, 2012;da Silva Junior et al, 2019;Diaz Lara et al, 2014), this was not reflected in the match pace characteristics in our sample. A likely reason is that each athlete was matched with an opponent of similar skill and experience level, which may negate any major differences in athletic ability.…”
Section: Discussionmentioning
confidence: 69%
“…It could be related to the training status of fighters (recreational level) from this study, which includes fighters with low training volume in GCS (e.g., three to five sessions/week with sessions lasting ~75 min). In contrast, international and national GCS athletes commonly train ~3 times a day, including GCS training modalities (e.g., technical, specific exercises, and sparring) and strength/conditioning sessions [ 27 ]. Supporting this notion, most fighters (8 of 11) in this study were not engaged in systematic strength training, especially aimed at maximal strength development.…”
Section: Discussionmentioning
confidence: 99%
“…We found higher reps in all sets of the JJAPT in advanced athletes compared with novices. Previous studies have already demonstrated higher performance in the BJJ-specific strength test (Kimono Grip Strength Test) (31) and generic tasks (e.g., handgrip strength and vertical jump height) (17) in advanced BJJ athletes compared with novices. We also verified a high area under the ROC curve (>0.70), showing a high probability of correctly discriminating advanced from novice BJJ athletes using the total number of reps in the JJAPT.…”
Section: Discussionmentioning
confidence: 99%
“…The age, anthropometric characteristics, and years of BJJ experience are presented in Table 1. The novice athletes were considered as blue to purple belts, and the advanced athletes should have brown to black belts (31). In addition, the advanced athletes showed a higher time of experience than novices ( p < 0.001).…”
Section: Methodsmentioning
confidence: 99%